THE OPTIMUM DOSE OF NICOTINAMIDE FOR PROTECTION OF PANCREATIC P-CELLS AGAINST THE CYTOTOXIC EFFECT OF STREPTOZOTOCIN IN ALBINO RAT - HASSAN, NUZHAT; JANJUA, MUHAMMAD ZAHOOR (Journal of Ayub Medical College Abbottabad, 2001)
Background: The natural course of Insulin Dependent Diabetes Mellitus is characterized by progressive destruction of insulin producing (3-cells of the pancreas resulting from an autoimmune process. The toxic effect of some p-cells toxins like Streptozotocin (used to produce animal models of 1DDM) has been associated with the oxidative stress due to enhanced DNA repair and NAD depletion in damaged Î² -cells. This activity of Streptozotocin has been prevented with the use of nicotinamide. Methods: A light microscopic study was designed to determine the optimum dose of nicotinamide required for protection of pancreatic Î²-cells against the toxicity of Streptozotocin. 35 adult male albino rats were divided into five equal groups A, L>. C. D and E. the duration of study was 14 days. The animals in experimental groups C, D and E received a single intraperitoneal! injection of nicotinamide 250 mg/Kg, 350 mg/Kg and 500 mg/Kg respectively on day one. Animals in group A and B acted as normal control and diabetic control respectively. All the animals except those in group A received simultaneous injection of Streptozotocin 32 mg/Kg body weight intraperitoneally in a single dose. Fasting blood glucose was assessed and the animals weighed before starting the treatment, after 48 hours and at the end of the experimental period. Histological studies were carried out at the end of the study period. Results: The blood glucose level and the final body weight of the animals in group C matched the values in diabetic control. Histologically the pancreas had generally reduced p-cells mass (P < 0.001) with altered morphology. The animals in group D showed impaired glucose tolerance at 48 hours but were normoglycaemic at the end of the study period. There was some loss of p-cells but a significant number of these cells (P < 0.05) showing normal morphology were saved. The animals in group E had normal number of p-cells having normal morphological features. The final body weight and fasting blood glucose of these animals matched the values in normal control (group A). Conclusions: These data suggest that the optimum dose of nicotinamide in regard to prevention against the p-cytotoxic effect of Streptozotocin in albino rat is 500 mg/Kg body weight.